RETRACTED: The diversity of the higher algae of Lake Kumsulton - Pardayev Sh.; Shamsiyev N.A.; Toshev H.M.; Sanoyeva Kh.O.; Rakhmonov N.R.; Tuymurodova Sh.Sh. (E3S Web of Conferences, 2024)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001